Classification Analysis using CNN and LSTM on Wheezing Sounds - Gustav Bagus Samanta (International Journal on Information and Communication Technology (IJoICT), 2022)
Asthma is a public health problem in almost all countries in the world. One of the symptoms that exist in asthmatics is wheezing. In several studies, wheezing has been classified using classification algorithm. However, the implemented classification algorithm still has a low level of accuracy. This study aims to determine the accuracy of the results from wheezing classification of respiratory sounds by comparing the algorithm.